Temporal trends and patterns in heart failure incidence: a population-based study of 4 million individuals - Conrad, N; Judge, A; Tran, J; Mohseni, H; Hedgecott, D; Perez Crespillo, A; Allison, M; Hemingway, H; Cleland, J; McMurray, J; Rahimi, K (Lancet, 2017)
Background: Large-scale and contemporary population-based studies of heart failure incidence are needed to inform resource planning and research prioritisation but current evidence is limited. Methods: We used linked primary and secondary electronic health records of 4 million individuals from the Clinical Practice Research Datalink (CPRD), a cohort that is representative of the UK population in terms of age and sex. We investigated characteristics of patients with incident heart failure (mean age, 77 years; 49% women), as well as temporal trends in heart failure incidence and prevalence by age, sex, socioeconomic status and region from 2002 to 2014. Findings: Over the study period, age-sex-standardised heart failure incidence rates declined, similarly for men and women, by 7%. However, the absolute number of individuals with newly diagnosed heart failure increased by 12%, largely due to an increase in population size and age. The absolute number of prevalent heart failure cases increased even more strongly, by 23%. Over the study period, patients’ age and multi-morbidity at first heart failure presentation increased. Socio-economically deprived individuals were 61% more likely to develop heart failure and did so 3.5 years earlier in life than those from the most affluent group. From 2002 to 2014, the socio-economic gradient in age at first presentation with heart failure widened. Socio-economically deprived individuals also had more co-morbidities, despite their younger age. Interpretation: Despite a moderate decline in standardized heart failure incidence, the burden of heart failure in the UK is increasing, and is now similar to the four most common causes of cancer combined. The observed socio-economic disparities in disease incidence and age at onset within the same nation point to a potentially preventable nature of heart failure that still needs to be tackled.